Compound doped copper calcium titanate giant dielectric ceramic material and preparation method thereof
By doping LCNO into CCTO, the giant dielectric ceramic material of (1-x)CCTO-xLCNO is formed, which solves the problem of high dielectric loss in the high frequency band of CCTO-based ceramics, and achieves significant improvement in dielectric constant and improvement in high frequency relaxation behavior, and has wide application potential.
Patent Information
- Application Number
- CN202510185511.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The advantages and disadvantages of the dielectric loss mechanism of CCTO-based ceramics at different frequencies have resulted in the optimization of their dielectric performance, especially in the high frequency band, which limits their application in capacitors, energy storage devices and electronic equipment.
By doping LiCuNb3O9 (LCNO) into CCTO, a giant dielectric ceramic material with (1-x)CCTO-xLCNO is formed. The material is prepared by solid phase reaction method to improve the microstructure of the ceramic and reduce high-frequency dielectric loss.
It significantly improves the huge dielectric constant response and high-frequency relaxation behavior, effectively reduces the high-frequency dielectric loss, and reaches 105 at 20Hz, and has broad application prospects in dielectric components of high-frequency capacitors, energy storage devices and electronic equipment.
Smart Images

Figure CN119822811A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dielectric functional ceramics, and in particular to a compound-doped calcium copper titanate giant dielectric ceramic material and a preparation method thereof. Background Art
[0002] The development of high-performance dielectric materials has had a profound impact on the current power electronics industry, new energy technology and artificial intelligence. 3 ) materials have attracted much attention due to their great potential in 5G communications, high energy density storage and device miniaturization. 12 , referred to as CCTO) ceramics are typical giant dielectric constant materials (up to 10 at room temperature 4 ), and in the wide temperature range of 100-600K and 10 2 -10 6 Hz wide frequency domain. However, the large dielectric loss of CCTO ceramics seriously restricts its practical application. The internal barrier layer capacitor (IBLC) model proposed by Sinclair et al. can effectively explain the giant dielectric constant characteristics of CCTO ceramics. According to the IBLC theory, in order to reduce dielectric loss and maintain stability, researchers have optimized the dielectric properties of CCTO by various means. Among them, compound doping is one of the effective strategies to optimize CCTO ceramics. For example: doping In 0.05 Nb 0.05 Ti 0.90 O 12 (INTO) can enhance the grain boundary insulation, making CCTO / INTO system maintain high dielectric constant (5.0×10 3 -8.6×10 3 ) while reducing its dielectric loss (0.029-0.046. Composite ACTO family compounds (Y 2 / 3 Cu3Ti4O 12 、SrCu3Ti4O 12 、Bi 2 / 3 Cu3Ti4O 12 ) significantly optimizes dielectric properties by regulating interface states and grain boundary characteristics. Our previous research also showed that adding 0.1Na 0.5 Bi 0.5 TiO3-0.9BaTiO3, SrTiO3, and ZnO can improve relaxation behavior and achieve excellent dielectric properties. However, the dielectric loss mechanisms of CCTO-based ceramics vary at different frequencies, limiting the optimization of their dielectric properties. Therefore, the development of new CCTO-based giant dielectric ceramic materials is imperative.
[0003] LiCuNb3O9 (LCNO) ceramics with distorted perovskite structure also exhibit giant dielectric constant (~10 4 ) and significant relaxation characteristics, the mechanism of which is similar to the grain boundary response of CCTO. + The introduction of 2+ Site (ionic radius matching: Li + 0.076nm and Ca 2+ 0.100nm) to alleviate lattice distortion; Nb 5+ Replace Ti 4+ The oxygen vacancy concentration can be reduced. In addition, Cu 2+ The enrichment at the grain boundaries may form a high-resistance interface layer. The introduction of LCNO is expected to achieve new breakthroughs in the dielectric response, relaxation characteristics and loss control of CCTO-based ceramics, but related research has not yet been reported. Summary of the Invention
[0004] The purpose of the present invention is to provide a compound-doped copper calcium titanate giant dielectric ceramic material and a preparation method thereof, which can significantly improve high-frequency relaxation behavior while obtaining a giant dielectric constant, thereby reducing high-frequency dielectric loss.
[0005] To achieve the above objectives, the present invention provides a compound-doped calcium copper titanate giant dielectric ceramic material, wherein the general formula of the compound-doped calcium copper titanate giant dielectric ceramic is (1-x)CCTO-xLCNO, wherein 0≤x≤0.15; CCTO is a lead-free perovskite-type calcium copper titanate ceramic, and LCNO is a LiCuNb3O9 ceramic.
[0006] The present invention also provides a method for preparing the compound-doped calcium copper titanate giant dielectric ceramic material, comprising the following steps:
[0007] (1) Li2CO3 powder, CaCO3 powder, Nb2O5 powder, CuO powder and TiO2 powder are used as raw materials and the ingredients are prepared according to the stoichiometric ratio of (1-x)CCTO-xLCNO to obtain a mixed powder;
[0008] (2) placing the mixed powder obtained in step (1), zirconium oxide ball milling media, and anhydrous ethanol in a nylon ball milling jar, and uniformly mixing the raw materials by planetary ball milling; after the ball milling is completed, the grinding balls and the slurry are separated by a sieve, and the obtained slurry is vacuum-dried at 80-90° C. for 12-24 hours, and then further ground and sieved to finally obtain a precursor powder with uniform particle size distribution;
[0009] (3) placing the precursor powder obtained in step (2) in a high-purity alumina crucible, isolating the atmosphere with a sealed cover, and then pre-sintering the powder in a box furnace. After the solid-phase reaction is complete, the powder is cooled to room temperature with the furnace, and subjected to secondary ball milling, drying, and grinding to obtain (1-x)CCTO-xLCNO pre-sintered powder;
[0010] (4) preparing a polyvinyl alcohol solution as a binder, adding it to the pre-calcined powder obtained in step (3) for granulation, and passing it through a 60-mesh and a 100-mesh sieve to obtain uniform particles;
[0011] (5) The uniform particles after passing through a 100-mesh sieve are placed in a mold for green pre-pressing to form a disc sample, which is then placed in a cold isostatic press and held at a pressure of 200-250 MPa for 2-3 minutes before being taken out to obtain a (1-x)CCTO-xLCNO green sample;
[0012] (6) The green disc sample obtained in step (5) is placed in a crucible in a muffle furnace and kept at 550-600°C for 5-10 hours for green body debinding. After debinding, the sample is placed in a muffle furnace for ceramic sintering and kept in an air atmosphere at 1080-1100°C for 6-10 hours. After cooling to room temperature with the furnace, the sample is taken out. Finally, the sintered ceramic is ground, polished, and a silver electrode is made to obtain a (1-x)CCTO-xLCNO ceramic sample.
[0013] Preferably, in step (2), the mass ratio of the mixed powder to the zirconium oxide ball milling medium is 1:(3-3.5), and the mass ratio of the mixed powder to anhydrous ethanol is 1:(1.2-1.4); the ball milling speed is 450-550 rpm, and the ball milling time is 6-8 hours.
[0014] Preferably, in step (3), the powder is pre-calcined by heating the powder from room temperature to 850-1000° C. at a heating rate of 3-5° C. / min and keeping the temperature for 8-10 hours.
[0015] Preferably, in step (4), the mass fraction of the polyvinyl alcohol solution is 5.5 to 9.5 wt.%, and the mass volume ratio of the calcined powder to the polyvinyl alcohol solution is 4 g: (1-2) ml.
[0016] Preferably, in step (5), the diameter of the disc-shaped sample is 10-12 mm and the thickness is 1-1.5 mm.
[0017] Preferably, in step (6), the silver electrode is prepared by applying silver paste on the polished ceramic and calcining the silver at 550° C. for 20 minutes.
[0018] Therefore, the present invention adopts the above-mentioned compound doped calcium copper titanate giant dielectric ceramic material and its preparation method, which has the following beneficial effects: the present invention adopts the solid phase reaction method to prepare LCNO-CCTO giant dielectric ceramic material, the preparation method is simple and controllable, improves the microstructure of the ceramic, obtains ceramics with good density, and can obtain excellent dielectric properties, with a dielectric constant of up to 10 at 20Hz. 5 , high-frequency dielectric loss is significantly reduced, and it has broad prospects in high-frequency capacitors, energy storage devices and dielectric components in electronic equipment.
[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of (1-x)CCTO-xLCNO ceramic materials prepared in Examples 1-4 of the present invention;
[0021] Figure 2 SEM micromorphologies of the (1-x)CCTO-xLCNO ceramic materials prepared in Examples 1-4 of the present invention, wherein (a) is a SEM micromorphology of the ceramic material prepared in Example 1 when x = 0, (b) is a SEM micromorphology of the ceramic material prepared in Example 2 when x = 0.05, (c) is a SEM micromorphology of the ceramic material prepared in Example 3 when x = 0.10, and (d) is a SEM micromorphology of the ceramic material prepared in Example 4 when x = 0.15;
[0022] Figure 3 The room temperature dielectric constant of the (1-x)CCTO-xLCNO ceramic material prepared in Examples 1-4 of the present invention varies with frequency;
[0023] Figure 4 This is a graph showing the room temperature dielectric loss versus frequency of the (1-x)CCTO-xLCNO ceramic materials prepared in Examples 1-4 of the present invention;
[0024] Figure 5 This is a comparison chart of the room temperature dielectric constant and dielectric loss of the (1-x)CCTO-xLCNO ceramic materials prepared in Examples 1-4 of the present invention at 20 Hz. DETAILED DESCRIPTION
[0025] Unless otherwise defined, technical or scientific terms used in the present invention shall have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0027] Furthermore, it should be understood that although this specification describes the embodiments, not every embodiment includes only one independent technical solution. This description is for clarity only. Those skilled in the art should consider the specification as a whole. The technical solutions in the various embodiments may also be appropriately combined to form other embodiments that are understandable to those skilled in the art. These other embodiments are also encompassed within the scope of protection of the present invention.
[0028] Example 1
[0029] This embodiment provides a compound-doped calcium copper titanate giant dielectric ceramic material, the general formula of which is (1-x)CCTO-xLCNO. In this embodiment, x=0. The preparation method is as follows:
[0030] Li2CaO3 powder, CaCO3 powder, Nb2O5 powder, CuO powder and TiO2 powder were weighed as raw materials by stoichiometric method. 12 The ingredients are prepared according to the chemical measurement; the mixed powder and zirconia ball milling beads are loaded into a nylon ball mill at a ratio of 1.4, and a certain amount of anhydrous ethanol (the mass ratio of anhydrous ethanol to the mixed raw materials is 1.3:1) is added and placed in a planetary ball mill for wet ball milling at a speed of 550 rpm for 20 hours; then a uniform precursor powder is obtained after drying, grinding and sieving.
[0031] The precursor powder obtained in step (1) was placed in a zirconia crucible, and then placed in a box furnace for powder pre-sintering. The temperature was raised from room temperature to 1000°C at a heating rate of 4°C / min, kept warm for 10 hours, and cooled to room temperature with the furnace. CCTO pre-sintered powder was obtained by secondary ball milling, drying and grinding.
[0032] After the pre-calcined powder was ball-milled twice, dried and ground, a polyvinyl alcohol (PVA) solution with a mass fraction of 5.5 wt.% was added to the ground powder as a binder for granulation. After passing through 60-mesh and 100-mesh sieves, the uniform powder particles passed through the 100-mesh sieve were placed in a stainless steel mold with a diameter of 10 mm, pre-pressed on a conventional tablet press, and then maintained at a pressure of 250 MPa for 2 minutes to prepare a cylindrical green sample with a diameter of 10 mm and a thickness of 1.2 mm.
[0033] The zirconia crucible containing the cylindrical green sample was placed in a high-temperature muffle furnace for debinding, and the temperature was raised from room temperature to 550°C, kept warm for 6 hours, and then sintered in an air atmosphere at 1100°C for 10 hours. After cooling to room temperature with the furnace, the sample was taken out and subsequently ground and polished to make a silver electrode (after applying silver paste, silver was sintered at 550°C for 20 minutes, and the silver paste was commercially available silver paste). Finally, the CCTO ceramic sample was obtained and its electrical properties were tested.
[0034] Example 2
[0035] This embodiment provides a compound-doped calcium copper titanate giant dielectric ceramic material, the general formula of which is (1-x)CCTO-xLCNO. In this embodiment, x=0.05. The preparation method is as follows:
[0036] Li2CaO3 powder, CaCO3 powder, Nb2O5 powder, CuO powder and TiO2 powder were weighed as raw materials by stoichiometric method, and the mixture was prepared according to the formula of 0.05LiCuNb3O9-0.95CaCu3Ti4O 12 , that is, the stoichiometric ingredients are prepared according to 0.05LCNO-0.95CCTO; the powder pre-sintering process is: heating from room temperature to 950°C and keeping warm for 8 hours; the ceramic sintering process is: heating from room temperature to 1090°C, keeping warm for 8 hours, and then cooling with the furnace to obtain a 0.05LCNO-0.95CCTO ceramic sample; the remaining steps are the same as those in Example 1.
[0037] Example 3
[0038] This embodiment provides a compound-doped calcium copper titanate giant dielectric ceramic material, the general formula of which is (1-x)CCTO-xLCNO. In this embodiment, x=0.10. The preparation method is as follows:
[0039] Li2CaO3 powder, CaCO3 powder, Nb2O5 powder, CuO powder and TiO2 powder were weighed as raw materials by stoichiometric method, and the mixture was prepared according to the formula of 0.1LiCuNb3O9-0.9CaCu3Ti4O 12 , that is, the stoichiometric ingredients are prepared according to 0.1LCNO-0.9CCTO; the powder pre-sintering process is: heating from room temperature to 900°C and keeping warm for 8 hours; the ceramic sintering process is: heating from room temperature to 1080°C, keeping warm for 8 hours, and then cooling with the furnace to obtain a 0.1LCNO-0.9CCTO ceramic sample; the remaining steps are the same as those in Example 1.
[0040] Example 4
[0041] This embodiment provides a compound-doped calcium copper titanate giant dielectric ceramic material, the general formula of which is (1-x)CCTO-xLCNO. In this embodiment, x=0.20. The preparation method is as follows:
[0042] Li2CaO3 powder, CaCO3 powder, Nb2O5 powder, CuO powder and TiO2 powder were weighed as raw materials by stoichiometric method, and the mixture was prepared according to the formula of 0.15LiCuNb3O9-0.85CaCu3Ti4O 12, that is, the stoichiometric ingredients are 0.1LCNO-0.9CCTO; the powder pre-sintering process is: heating from room temperature to 850°C and keeping warm for 6 hours; the ceramic sintering process is: heating from room temperature to 1080°C, keeping warm for 6 hours, and then cooling with the furnace to obtain a 0.15LCNO-0.85CCTO ceramic sample; the remaining steps are the same as those in Example 1.
[0043] The XRD patterns of the (1-x)CCTO-xLCNO ceramic materials prepared in the above examples 1-4 are shown in the attached specification. Figure 1 As shown in the figure, the diffraction peaks of all LCNO-CCTO ceramic samples are consistent with the perovskite cubic phase structure of CCTO, indicating that LCNO is dissolved into the CCTO lattice in the form of ions. At the same time, the formation of CuO second phase was found, and the diffraction peak intensity gradually increased with the increase of LCNO doping amount. The lattice constants of all samples were calculated based on the XRD patterns and are:
[0044] The SEM micromorphology of the (1-x)CCTO-xLCNO ceramic material prepared in the above examples 1-4 is shown in the attached specification. Figure 2 As shown in the figure, the grains of pure CCTO are coarser than those of the (1-x)CCTO-xLCN ceramic sample. This may be because the copper liquid phase formed during the sintering process of undoped CCTO will increase the grain boundary mobility, thereby causing the grain size to grow. After doping with LCN, the grain size of CCTO ceramics decreases sharply, and the morphology of the grains changes to a certain extent, with the grains appearing blocky or granular. By applying the lattice constants of the four samples obtained, the theoretical density of the samples is calculated, and compared with the actual density, the relative densities of the four samples are 93.8%, 97.1%, 96.6%, and 96.9%, respectively. It can be found that the addition of LCN reduces the grain size of CCTO, which also increases the density of the ceramic sample.
[0045] The room temperature dielectric constant of the (1-x)CCTO-xLCNO ceramic material prepared in the above examples 1-4 varies with frequency as shown in the attached specification. Figure 3 As shown in the figure, compared with pure CCTO ceramics, the dielectric constant of LCNO-CCTO ceramics is improved to varying degrees in different frequency bands. At 20 Hz, the dielectric constant of all LCNO-CCTO ceramics (~10 5 ) are higher than those of pure CCTO ceramics, and the two ceramic samples with x = 0.10 and x = 0.15 show relatively good frequency stability.
[0046] The room temperature dielectric loss curve of the (1-x)CCTO-xLCNO ceramic material prepared in the above examples 1-4 as a function of frequency is shown in the attached specification. Figure 4As shown in the figure, compared with pure CCTO ceramics, the dielectric loss of LCNO-CCTO ceramics in the medium and low frequency regions is increased, but the dielectric loss in the high frequency band is significantly reduced.
[0047] The room temperature dielectric constant and dielectric loss comparison diagram of the (1-x)CCTO-xLCNO ceramic materials prepared in the above examples 1-4 at 20Hz is shown in the attached specification. Figure 5 As shown in the figure, with the increase of LCNO doping amount, the dielectric constant of the ceramic material increases from 1.06×10 5 Increased to 4.64×10 5 , while the dielectric loss shows a trend of increasing and then decreasing.
[0048] Therefore, the present invention prepares LCNO-doped CCTO lead-free ceramics, which significantly enhances the giant dielectric constant response and high-frequency relaxation behavior, effectively reduces high-frequency loss, and has potential application prospects as dielectric components in high-frequency capacitors, energy storage devices and electronic devices.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A compound-doped copper calcium titanate giant dielectric ceramic material, characterized in that: The compound-doped calcium copper titanate giant dielectric ceramic has a general formula of (1-x)CCTO-xLCNO, wherein 0≤x≤0.15; CCTO is a lead-free perovskite-type calcium copper titanate ceramic CaCu3Ti4O 12 , LCNO is LiCuNb3O9 ceramic.
2. A method for preparing the compound-doped calcium copper titanate giant dielectric ceramic material as claimed in claim 1, characterized in that: The following steps are involved: (1) Li2CO3 powder, CaCO3 powder, Nb2O5 powder, CuO powder and TiO2 powder are used as raw materials and mixed according to the stoichiometric ratio of (1-x)CCTO-xLCNO to obtain a mixed powder; (2) placing the mixed powder obtained in step (1), zirconium oxide ball milling media and anhydrous ethanol in a nylon ball milling jar, and uniformly mixing the raw materials by planetary ball milling; after the ball milling is completed, the grinding balls and the slurry are separated by a sieve, and the obtained slurry is vacuum dried at 80-90° C. for 12-24 hours, and then further ground and sieved to finally obtain a precursor powder with uniform particle size distribution; (3) placing the precursor powder obtained in step (2) in a high-purity alumina crucible, using a sealed cover to isolate the atmosphere, and then pre-sintering the powder in a box furnace. After the solid phase reaction is complete, the powder is cooled to room temperature with the furnace, and the (1-x)CCTO-xLCNO pre-sintered powder is obtained by secondary ball milling, drying and grinding; (4) preparing a polyvinyl alcohol solution as a binder, adding it to the pre-calcined powder obtained in step (3) for granulation, and passing it through a 60-mesh and 100-mesh sieve to obtain uniform particles; (5) placing the uniform particles after passing through a 100-mesh sieve in a mold for green pre-pressing to form a disc-shaped sample, and then placing it in a cold isostatic press, holding the pressure at 200-250 MPa for 2-3 minutes, and then taking it out to obtain a (1-x)CCTO-xLCNO green sample; (6) The green disc sample obtained in step (5) is placed in a crucible in a muffle furnace, and is kept at 550-600°C for 5-10 hours for green body debinding. After debinding, the sample is placed in a muffle furnace for ceramic sintering, and is kept in an air atmosphere at 1080-1100°C for 6-10 hours. After cooling to room temperature with the furnace, the sample is taken out, and finally the sintered ceramic is ground, polished, and a silver electrode is made to obtain a (1-x)CCTO-xLCNO ceramic sample.
3. The method for preparing a compound-doped calcium copper titanate giant dielectric ceramic material according to claim 2, characterized in that: In step (2), the mass ratio of the mixed powder to the zirconium oxide ball milling medium is 1:(3-3.5), and the mass ratio of the mixed powder to anhydrous ethanol is 1:(1.2-1.4); the ball milling speed is 450-550 rpm, and the ball milling time is 6-8 hours.
4. The method for preparing a compound-doped calcium copper titanate giant dielectric ceramic material according to claim 1, characterized in that: In step (3), the powder is pre-sintered by heating the temperature from room temperature to 850-1000°C at a heating rate of 3-5°C / min and keeping the temperature for 8-10 hours.
5. The method for preparing a compound-doped calcium copper titanate giant dielectric ceramic material according to claim 2, characterized in that: In step (4), the mass fraction of the polyvinyl alcohol solution is 5.5-9.5wt.%, and the mass volume ratio of the pre-calcined powder to the polyvinyl alcohol solution is 4g:(1-2)ml.
6. The method for preparing a compound-doped calcium copper titanate giant dielectric ceramic material according to claim 2, characterized in that: In step (5), the diameter of the disc-shaped sample is 10-12 mm and the thickness is 1-1.5 mm.
7. The method for preparing a compound-doped calcium copper titanate giant dielectric ceramic material according to claim 2, characterized in that: In step (6), the silver electrode is prepared by applying silver paste on the polished ceramic and calcining the silver at 550° C. for 20 minutes.
Citation Information
Patent Citations
Low temperature sintered giant dielectric ceramic capacitor medium and preparation method thereof
CN103508730A
Giant dielectric low-loss CCTO-based ceramic material and preparation method thereof
CN106673642A
Lithium-bismuth co-doped copper cadmium titanate giant dielectric ceramic material and preparation method thereof
CN106747411A
Giant dielectric composite ceramic copper calcium titanate material and preparation method and application thereof
CN109650875A
Ceramic with giant dielectric constant and low dielectric loss and preparation method thereof
CN114436643A